Virtual assessment of a possible meningioma in a Roman-period cranium - Daniel Rodríguez-Iglesias; Ana Pantoja-Pérez; Pilar Fernández-Colón; Adrián Pablos; Manuel Alcaraz-Castaño; Nohemi Sala (Virtual Archaeology Review, 2023)
Diseases have accompanied human populations since prehistoric times. Knowing the paleopathologies and their consequences derived from them can help us to understand their impact and how have been decisive in our ancestors' ways of life. Taphonomic and paleopathological studies are key to understanding how injuries occurred; they can provide information on causes of death, analyzed populations behaviour, such as the existence of interpersonal conflicts or how they took the care of the sick. Those studies also confirm the existence of certain diseases, mentioned in the archaeological record. This paper explains the analysis of four lesions found in a Roman-era cranium from Sima de Marcenejas, located in Northern Spain. An anthropological analysis of this cranium has revealed that it corresponds to an adult male individual. This work focuses on the differential diagnosis of the lesions, to be able to discern the most likely aetiologies. The following techniques have been implemented: classical morphological analysis, forensic taphonomic analysis and virtual analysis. MicroCT and 3D microscopy have been used as essential tools for the virtual analysis of the cranium and its lesions. The results obtained revealed the existence of a tumour and three exocranial traumas, all of them antemortem. The location of the tumour, as well as its morphology together with other aspects, support the meningioma as the most probable tumour type. This possible ancient meningioma represents the first case for these chronologies on the Iberian Peninsula, where there are few documented cases. The three traumatic lesions reveal the existence of injuries produced by both, blunt and sharp objects, related to events of interpersonal violence. By applying virtual 3D analyses, the researchers have demonstrated that it is viable to identify tumours in those internal cranial regions, where the lesion is not visible, thus providing new comparative data for the paleopathological record of past populations.